Consequences of different cutting regimes on regrowth and nutrient stoichiometry of Sparganium erectum L. and Potamogeton natans L. (6th September 2017) - Bal, K.D.; Verschoren, V.; Sara, J.R.; Meire, P.; Schoelynck, J.
Abstract: Aquatic vegetation forms an essential component in freshwater ecosystems but due to changed environmental and anthropogenic conditions often needs management to reduce nuisance for human land‐use. In this paper, the authors looked at the regrowth of two macrophyte species ( Potamogeton natans and Sparganium erectum ) in two lowland rivers under different cutting treatments. After an initial cross‐sectional transect was manually removed from bank to bank at the beginning of the growth season, a monthly repetitive removal of biomass in plots on that transect was done during the rest of the growth season (testing frequency of mowing). Additional new transects were also cut in subsequent months (testing timing of mowing). Finally, biomass was repetitively removed in plots in those additional transects too (testing frequency of mowing × timing of mowing). The biomass at the end of the growth season was analysed for C, N, P, and Si. It was demonstrated that timing and frequency of vegetation cutting has an important effect on the capacity and rate of species' recovery and therefore on the efficiency of the applied management. Nutrient stoichiometry of the regrown biomass was directly affected by cutting. Caused by differences in the applied timing and frequency of the cutting, C/N and N/P ratios and BSi concentrations were highly variable. Yet, overall, there was a clear tendency towards a higher C/N ratio and BSi concentration and lower N/P ratio in biomass that recovered after cutting. This human impact on the quantity and quality of autochthonous organic matter may have knock‐on effects on the decomposers food web and mineralization process.